Value of Evidence of Arguments Via Whatsapp in Divorce Cases in Court - Hasbuddin Khalid; Jasmaniar Jasmaniar; Andika Prawira Buana (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
This paper aims to analyze the value of evidence of quarrels through the whatsapp application in divorce proceedings in court. This research is normative research with a statutory approach. Types and sources of legal materials are primary legal materials, secondary legal materials, and tertiary legal materials. The results of the research that quarrels carried out through the WhatsApp application can be submitted as evidence at trial, however, the value of evidence is not perfect and binding so that other evidence is needed to prove disputes and quarrels that occur continuously as a cause of divorce